Scientific production of the Cuban Journal of Dentistry: 2009-2013 - Josefa Dolores Miranda Tarragó; Lourdes Hernández Cuétara; Eglys Trujillo Miranda; Irene Rodríguez Pérez; Luisa Haydee Alfonso Dreke (Editorial Ciencias Médicas, 2015)
Introduction: bibliometric indicators allow characterizing the scientific production of a journal. Objective: describe the scientific production of the Cuban Journal of Dentistry from 2009 to 2013. Method: a descriptive, transversal study was conducted. All articles published in the Cuban Journal of Dentistry from 2009 to 2013 were selected. The type and number of papers, thematic, authors and their country of origin, bibliographyc updating, and the impact factor were variables studied. SciELO Cuba was used to obtain the information. The absolute frequencies and the percentage from the descriptive statistics were used. The results obtained were presented in tables and graphs for their better interpretation. Results: 226 papers were published, 114 were original articles, 20 were bibliographic reviews, 60 were report of clinical case, 14 were on pedagogy and history, and 18 on others. There were 758 authors: 161 Cuban authors, 43 Brazilian, 11 Colombian, 4 Mexicans, 3 Chileans, 2 Venezuelans, 1 Argentines and 1 Peruvian. 93 articles were on oral surgery, 87 on epidemiology of oral diseases, 14 on history and pedagogy, 11 on community health, 7 on natural and traditional medicine, 14 on other topics. The 2009 impact factor was 0.1795 and 0.3394 in 2013. Conclusions: a significant number of items have been published from 2009 to 2013; there was predominance of original articles and case presentations, the Cuban and Brazilian authors were highlighted; updated references and impact factor discreetly showed a upward trend.